(untitled) - Roberts, Larry S. (Boston, 2005)
A parasitology text for biology and/or zoology students at the undergraduate level. Emphasizes principles with related information on the biology, physiology, morphology, and ecology of the major parasites of humans and domestic animals. This is not a diagnostic manual for medical students. .
Keywords: Parasitology,Khoa vật ký sinh